Beautiful warrior : the legend of the Nun's kung fu - McCully, Emily Arnold (New York : Arthur A. Levine Books, 1998)
Tells the story of two unlikely kung fu masters and how their skill in martial arts saves them both.
Wilson's Children
School Library Journal starred
Notable/Best Books (A.L.A.)
4.8
3-6
Keywords: Kung fu -- Fiction; Sex role -- Fiction; China -- Fiction; Kung fu -- Fiction; Sex role -- Fiction; China -- Fiction